Critical Literacy Pedagogy for Bilingual Preservice Teachers Exploring Social Identity and Academic Literacies - Cho, Hyesun (Springer Singapore, 2018)
This book presents a participatory action research study exploring the social identity and academic literacies of bilingual preservice teachers. It describes the transformative experiences of undergraduate students during their participation in a program specially designed to develop bilingual teachers in Hawaii, USA. Further, it discusses how the curriculum and instruction in the classroom provide a 'third space' for facilitating peer interaction and critical reflection on such issues as academic literacy, heritage language education, and teacher identity. In doing so, it connects ideas of social identity and academic literacies of bilingual preservice teachers to the "real work" of mentoring and teaching PreK-12 students themselves.